2017
DOI: 10.17116/otorino201782647-51
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors of allergic rhinitis among the children of the preschool age

Abstract: The objective of the present work was to estimate the prevalence and risk factors of the development of allergic rhinitis among the children at the age from 3 to 6 years. The cross-sectional study was carried out in five cities of the Altai region during the period from 2015 to 2016. The prevalence of allergic rhinitis was evaluated with the use of the Russian language version of the ISAAC questionnaire filled up by the parents of the children. A child whose parents answered in the affirmative to the question … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For all studies together, the total average score was 5 (SD = 1.89) out of 10. For the selection section, the mean score was 2 (SD = 1.2) out of 5, with only two studies [ 27 , 28 ] gaining the maximum number of points (5). In the comparability section, the mean score was 1 (SD = 0.2) out of 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all studies together, the total average score was 5 (SD = 1.89) out of 10. For the selection section, the mean score was 2 (SD = 1.2) out of 5, with only two studies [ 27 , 28 ] gaining the maximum number of points (5). In the comparability section, the mean score was 1 (SD = 0.2) out of 2.…”
Section: Resultsmentioning
confidence: 99%
“…The three pediatric asthma studies were all performed in Russia and included different, increasing age groups. Shakhova et al [ 28 ] included children aged three-to-six years and found 11.1% asthma-like symptoms in the Altai region, Russia. In this study they used the ISAAC questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation